Bioactivity-based analysis and chemical characterization of cytotoxic constituents from Chaga mushroom (Inonotus obliquus) that induce apoptosis in human lung adenocarcinoma cells. (5th October 2018) - Baek, Jiwon; Roh, Hyun-Soo; Baek, Kwan-Hyuck; Lee, Seulah; Lee, Seul; Song, Seong-Soo; Kim, Ki Hyun
Abstract: Ethnopharmacological relevance: Inonotus obliquus, also known as Chaga mushroom, is one of the most widely appreciated wild edible mushrooms in Russia and northern European countries and is renowned for its use in cancer treatment. Indeed, recently published in vitro and in vivo studies have demonstrated its anticancer activity in various types of cancer and support its potential application for therapeutic intervention in cancer. However, its activity against lung cancer, the most commonly diagnosed cancer and the leading cause of cancer death worldwide, and the underlying molecular basis of its action remain to be fully elucidated. Objective: This study aimed to evaluate the cytotoxic activity of I. obliquus in four human lung adenocarcinoma cell lines with different p53 status (A549, H1264, H1299, and Calu-6) and identify its active constituents by bioactivity-based analysis and the underlying molecular basis of their cytotoxicity on lung cancer cells. Materials and methods: Bioactivity-guided fractionation and preparative/semi-preparative HPLC purification were used with LC/MS analysis to separate the bioactive constituents. Cell viability and apoptosis in human lung cancer cell lines (A549, H1264, H1299, and Calu-6) were assessed using the WST-1 assay and TUNEL staining, respectively. Caspase activation was assessed by detecting its surrogate markers, cleaved poly (ADP-ribose) polymerase (PARP) and caspase-3, using an immunoblot assay. Results: The MeOH extract of I. obliquus reduced cell viability in all lung cancer cell lines tested through induction of apoptosis accompanied by caspase-3 cleavage. Bioactivity-guided fractionation of the MeOH extract and chemical investigation of its cytotoxic hexane-soluble and CH2 Cl2 -soluble fractions led to the isolation of eight triterpenoids (1–8 ), including a new lanostane-type triterpenoid named chagabusone A (7 ). The structures of the isolates were elucidated based on spectroscopic analysis, including 1D and 2D NMR and high-resolution ESIMS. Among isolated compounds, compounds 1, 6, and 7 showed the most potent cytotoxic activity in all human lung cancer cell lines examined, with IC50 values ranging from 75.1 to 227.4 μM. Cytotoxicity of these compounds was mediated by apoptosis with caspase-3 activation. Conclusion: These findings provide experimental evidence supporting the potential application of I. obliquus in lung cancer treatment and reveal the molecular basis underlying its cytotoxic activity against human lung cancer cells. Graphical abstract: fx1